Thinking forward through the past: Prospecting for urban order in (Victorian) public parks - Churchill, David (Theoretical criminology, 2018)
Supplementing familiar linear and chronological accounts of history, we delineate a novel approach that explores connections between past, present and future. Drawing on Koselleck, we outline a framework for analysing the interconnected categories of ‘spaces of experience' and ‘horizons of expectation' across times. We consider the visions and anxieties of futures past and futures present; how these are constituted by, and inform, experiences that have happened and are yet to come. This conceptual frame is developed through the study of the heritage and lived experiences of a specific Victorian park within an English city. We analyse the formation of urban order as a lens to interrogate both the immediate and long-term linkages between past, present and possible futures. This approach enables us to ground analysis of prospects for urban relations in historical perspective and to pose fundamental questions about the social role of urban parks.